GENDERED IMAGES IN ADVERTISING - Blakely, Kristin (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
For this assignment, you will be building upon the themes from the film viewed in class, "Killing Us Softly 3". You will need to find and reflect upon 6 advertisements from popular magazines or newspapers (print media only) and write a short report.